2017
DOI: 10.1098/rsbl.2017.0159
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable size-spectra stability in a marine system undergoing massive invasion

Abstract: The Mediterranean Sea is an invasion hotspot, with non-indigenous species suspected to be a major driver behind community changes. We used size spectra, a reliable index of food web structure, to examine how the influx of Red Sea fishes into the Mediterranean Sea has impacted the indigenous species community. This is the first attempt to use changes in the size spectra to reveal the effect of biological invasions. We used data from trawl catches along Israel's shoreline spanning 20 years to estimate changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…This latter observation confirms the results of several recent studies demonstrating that competition strength with alien species is not correlated to decreases in indigenous species abundance or richness (Givan et al 2018;Buba and Belmaker 2019). Furthermore, Buba et al (2017) demonstrated that over the same period of increase in alien abundance, indigenous fish size spectra in the eastern Mediterranean did not change. In a system at equilibrium and close to carrying capacity, a strong negative effect of alien species on the food web can be expected (Goren et al 2016;Corrales et al 2017).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This latter observation confirms the results of several recent studies demonstrating that competition strength with alien species is not correlated to decreases in indigenous species abundance or richness (Givan et al 2018;Buba and Belmaker 2019). Furthermore, Buba et al (2017) demonstrated that over the same period of increase in alien abundance, indigenous fish size spectra in the eastern Mediterranean did not change. In a system at equilibrium and close to carrying capacity, a strong negative effect of alien species on the food web can be expected (Goren et al 2016;Corrales et al 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Despite their large abundance and biomass, the effect of alien species on indigenous Mediterranean populations is still unclear. On one hand, the stability of fish size spectra (Buba et al 2017) and a lack of evidence for the competitive exclusion of indigenous species by alien species (Arndt et al 2018;Givan et al 2018; Buba and Belmaker 2019) suggest limited effects. On the other hand, alien species affect the local food-web structure, thus increasing the competition for local resources (Edelist et al 2013a;Goren et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[50,51]). However, recent studies showed that successful non-indigenous fishes preferentially occupy different functional niches than native ones, providing so far little support for active competitive exclusion of functionally similar species [52][53][54][55]. Additionally, the preliminary results of an ongoing functional trait study by our team of the same mollusc assemblages analysed here suggest little potential for active resource competition between native and non-indigenous assemblage components in the shallow subtidal [56].…”
Section: Discussion (A) Biodiversity Collapse and Its Causesmentioning
confidence: 61%
“…This suggests that other drivers, particularly regionally rapid seawater warming, might play a more significant role in native species' demise than previously thought (Albano et al, 2021;Givan et al, 2018;Rilov, 2016). Recent studies on Lessepsian fishes further support the secondary role of competitive displacement (Buba & Belmaker, 2019;Buba et al, 2017;Givan et al, 2018) and suggested that NIS indeed tend to occupy 'empty niches' (Azzurro et al, 2014;Givan et al, 2017), but none involved pre-invasion assemblage data.…”
Section: Introductionmentioning
confidence: 94%